Gusla: the origin and beyond - Duev, Ratko (Živa Antika & The Faculty of Philosophy, Skopje, 2011)
Although the general position within musicology is that all musical instruments originate from the Middle East, it is still possible that in the case of the gusla – at least regarding the way it was played, with a bow – that it was a Slavic innovation or a modification of a similar instrument. The theory of the bow’s origin from the nomadic people of Central Asia does not exclude the Slavs, who were in their vicinity and lived in a similar manner. The etymology of the term is the strongest proof concerning the specificity of the gusla. Compared to the other similar instruments, their names subsisted with certain variations among all the people who adopted them. For instance, the Sumerian pan-tur in Greece and Byzantium became pandoura and pandura in Rome, then the Semitic kinnor became kinyra, kithara in Greece, the Arabic rabab became rubab, rabob, robab, ribab, rbab, rababa, in Europe rebec, etc. It may be expected that the Slavs had some kind of a transcription of the rabab, the zither, or the Byzantine lyre, not their own terms which managed to subsist in spite of the strong influences of the musical traditions of the powerful empires throughout the medieval era and up to modern times.